Rice grain quality parameters and determination tools: a review on the current developments and future prospects - Sultana, Sharmin; Faruque, Muhiuddin; Islam, Md. Rafiqul (Informa UK Limited, 2022)
The determination of rice grain quality (RGQ) parameters is important because it is the benchmark of rice breeding success to meet up the consumers’ demand. RGQ includes milling, storage, cooking, eating, nutrition, and market quality of rice grain. Furthermore, demand for high-quality rice has increased globally and is expected to continue to rise due to consumer preferences. However, global consumer demand, culture, and demographic variances determine acceptable RGQ attributes. For example, European consumers prefer long-grain, nonaromatic rice, whereas Middle Eastern consumers prefer long-grain, well-milled rice with a strong aroma. To improve the rice quality, RGQ analysis is the best way; besides we need to understand the genetic mechanism of the several grain quality quantitative trait loci (QTLs) actions. A better understanding of these QTLs can be tremendously useful in the development of novel RGQ varieties. This review is intended to study major RGQ parameters and their assessment tools. This study is focusing on the limitations and prospects of QTLs to improve RGQ.